2009
DOI: 10.1167/iovs.08-3046
|View full text |Cite
|
Sign up to set email alerts
|

Tight Junction Transmembrane Protein Claudin Subtype Expression and Distribution in Human Corneal and Conjunctival Epithelium

Abstract: Claudin-1, -4, and -7 are expressed in corneal and conjunctival epithelia. Claudin-10 is prominent at several junctions between apical epithelial cells and goblet cells in conjunctival epithelium. Except for claudin-10 expression in conjunctival epithelium, the claudin subtype expressions of corneal and conjunctival epithelia are similar. Therefore, there must be a difference between these two epithelial types with regard to the specific ratio of claudin subtypes expressed or their phosphorylation status. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 36 publications
7
52
0
1
Order By: Relevance
“…They are the source of the gel mucin of the tears (MUC5AC) (Argüeso and Gipson, 2001). The tight junctions of the conjunctival epithelium are more leaky than those of the corneal epithelium, possibly, as noted, because of differences in the number and type of claudin subunits that they contain (Yoshida et al, 2009). In keeping with this, the paracellular channels demonstrated by electron microscopy are much wider than those of the corneal epithelium (Bron et al, 1997;Huang et al, 1989).…”
Section: Tight Junctionsmentioning
confidence: 95%
See 1 more Smart Citation
“…They are the source of the gel mucin of the tears (MUC5AC) (Argüeso and Gipson, 2001). The tight junctions of the conjunctival epithelium are more leaky than those of the corneal epithelium, possibly, as noted, because of differences in the number and type of claudin subunits that they contain (Yoshida et al, 2009). In keeping with this, the paracellular channels demonstrated by electron microscopy are much wider than those of the corneal epithelium (Bron et al, 1997;Huang et al, 1989).…”
Section: Tight Junctionsmentioning
confidence: 95%
“…Yoshida et al have summarized their role as structural components of Tjs in the corneal and the bulbar conjunctival epithelia (Yoshida et al, 2009). Despite the differences in permeability between these two epithelia they found that each epithelium expressed the same claudin subtypes, namely claudins 1, 4 and 7 throughout their thickness, although the expression of type 7 was superficial in the conjunctival epithelium.…”
Section: Tight Junctionsmentioning
confidence: 99%
“…Such a continuous permeability barrier functions through the formation of tight junctions that mediate adhesion between adjacent epithelial cells. 1 Tight junctions are composed of transmembrane proteins, including occludin, claudin, and a number of peripheral membrane structural proteins, such as zonula occludens (ZO), and are associated with a variety of regulatory proteins. 2 Disruption of these junctions is thought to perturb the normal cellular environment and lead to numerous pathological situations such as dry eye, asthma, and inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Tight junctions are multifunctional and dynamic protein complexes that connect adjacent cells by sealing the intercellular space between cells preventing the paracellular movement of solutes, ions and water. The main proteins forming a tight junction in the cornea are occludin (Langbein et al, 2002), claudins (Ban et al, 2003) and zonula occludens-1 (ZO-1) (Ban et al, 2003;Sosnova-Netukova et al, 2007;Yoshida et al, 2009). It was possible to measure the effect of Ap 4 A on tight junction proteins by western blot and the three mentioned proteins, claudin, occludin-7 and ZO-1, showed a clear reduction in its expression 2 h after the dinucleotide application, the fall of expression being 59.3% for ZO-1, 57.9% for occludin-7 and 58.8% for claudin (Loma et al, 2015b).…”
Section: Effect On Epithelial Permeabilitymentioning
confidence: 99%